A comparison of reproductive outcomes following hysteroscopic management versus dilatation and curettage of retained products of conception. Issue 1 (19th June 2014) - Ben‐Ami, Ido; Melcer, Yaakov; Smorgick, Noam; Schneider, David; Pansky, Moty; Halperin, Reuvit
Abstract: Objective: To compare the reproductive outcome of women who underwent blind dilatation and curettage (D&C) with those who underwent hysteroscopic resection of pathologically confirmed retained products of conception (RPOC). Methods: Medical records of women who underwent either D&C or hysteroscopic resection of RPOC at Assaf Harofeh Medical Center, Israel, between 2000 and 2010 were retrospectively reviewed. Results: A total of 177 women with pathologically confirmed RPOC underwent either D&C (n = 94, 53.1%) or hysteroscopy (n = 83, 46.9%). Mean time to conception was significantly shorter after hysteroscopy than after D&C (7.4 ± 7 vs 12.9 ± 16.8 months, P = 0.037). Rate of occurrence of a newly diagnosed infertility problem was significantly higher following D&C than hysteroscopy (23 [24.5%] vs 10 [12.0%]; P = 0.034). Etiology of the new problem was mechanical, including tubal occlusion and intrauterine adhesions. Logistic regression comparing both methods revealed that hysteroscopic resection was associated with a significant reduction in the occurrence of a new infertility problem compared with D&C (OR 0.42; 95% CI, 0.18–0.96, P = 0.04). Conclusion: Hysteroscopic removal of RPOC is associated with a shorter mean time to further conception and a lower rate of occurrence of newly diagnosed infertility problems than D&C.